2013
DOI: 10.12816/0003204
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Small Group Case-Based Learning on Traditional Pharmacology Teaching = أثر التعلم المبني على الحالات السريرية في مجموعات صغيرة لتدريس علم الأدوية على الطريقة التقليدية

Abstract: abstract:Objectives: This study aimed to measure medical students' perceptions of incorporating small group case-based learning (CBL) in traditional pharmacology lectures. Methods: Data were collected from third-year students (N = 68; 57% males, 43% females) at Al Quds University Medical School, Palestine. The students were offered a CBL-incorporated Pharmacology-2 course after they had been taught Pharmacology-1 in the traditional format during the preceding semester. Student attitudes towards the restructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Tayem concluded that CBL led to a significant improvement in students' self-reported analytical and communication skills, confidence, satisfaction, motivation and engagement. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Tayem concluded that CBL led to a significant improvement in students' self-reported analytical and communication skills, confidence, satisfaction, motivation and engagement. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The CBL encourages independent learning and deeper understanding of a particular topic and promotes life-long learning. 2,8,9…”
Section: Introductionmentioning
confidence: 99%
“…Problembased learning (PBL) and case-based learning (CBL) have emerged as powerful tools in reforming traditional teaching methods. PBL in medical education uses the patient's problem as a stimulator for students to learn problem-solving skills while CBL is a group discussion-styled teaching approach based on analysis of authentic clinical cases (Tayem, 2013;Jackson, 2003;Donner & Bickley, 1993;Finucane, Johnson & Prideaux, 1998). PBL and CBL engage students in their own learning, focus on concrete scenarios like problems or cases, and emphasize the development of thinking skills (Hofsten, Gustafsson & Haggstron, 2010;Chan, Hsu & Hong, 2008;Hakkarainen, Saarelainen & Ruokamo, 2007).…”
Section: Introductionmentioning
confidence: 99%